2018
DOI: 10.3389/fgene.2018.00628
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Profiling Identifies miR-125a and Its Target Gene Wnt2 in Skins of Different Haired Rabbits

Abstract: MicroRNAs (miRNAs) play critical roles in the control of skin and hair follicle development, epidermal homeostasis and pigmentation. However, the roles of miRNAs in the skins of rabbits with different hair types are unclear. In this study, we profiled miRNAs in the skins of long and short haired rabbits by Illumina deep sequencing. The dataset was compared with known mammalian miRNAs in miRBase 21.0. In total, 118 miRNAs were found to be differentially expressed between the two different rabbit types, of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Over 24 million clean reads were derived, which is consistent with recently reported results 22 . The read length distributions of two small RNA libraries, corresponding to distinct stages of hair follicle growth, demonstrated that 22-nt long sequences were the most represented, which was in accordance with the normal size of miRNAs reported in a previous study 32 .…”
Section: Discussionsupporting
confidence: 90%
“…Over 24 million clean reads were derived, which is consistent with recently reported results 22 . The read length distributions of two small RNA libraries, corresponding to distinct stages of hair follicle growth, demonstrated that 22-nt long sequences were the most represented, which was in accordance with the normal size of miRNAs reported in a previous study 32 .…”
Section: Discussionsupporting
confidence: 90%
“…The changes in expression compared with formulation buffer-treated cells were small, being the maximum fold increase of 1.58 (miR-34a) and the maximum fold decrease of 1.79 (miR-431) (Figure 3). Such a low differential expression (<2-fold) is not expected to have any appreciable biological relevance 14 , 15 . For each endogenous miRNA that was significantly differentially expressed, target transcripts were assessed in silico (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Such a low differential expression (<2-fold) is not expected to have any appreciable biological relevance. 14,15 For each endogenous miRNA that was significantly differentially expressed, target transcripts were assessed in silico (Table S1). RNA sequencing (RNA-seq) analysis confirmed that none of the target transcripts showed significant alterations, except for the Retrotransposon-like protein 1 (RTL1) transcript.…”
Section: Processing Of Mihtt In Hd Patient Ipsc-derived Neuronal Cultures Results In Guide Strand Expression Without Passenger Strand Actmentioning
confidence: 99%
“…When used in the detection of a gene of interest, the off-target effect of the crRNA may cause a false-positive result. To reduce the possible off-target–related false-positive results, we are using new programs [17], [18], [19] that particularly take consideration of on-target cutting efficiency to design crRNAs for specifically detecting HPV16 and 18, respectively.…”
Section: Discussionmentioning
confidence: 99%